PENGARUH E-COMMERCE, PENCATATAN AKUNTANSI, DAN KREDIT USAHA RAKYAT TERHADAP KEBERLANGSUNGAN USAHA UMKM KAIN TENUN TROSO DI JEPARA - Agus Setyono, David; Sunu Punjul Tyoso, Jaluanto; Khamimah, Khamimah; Soegiastuti, Janti (CV. Lafadz Jaya, 2024)
UMKM often faces conventional problems such as sales, financial management, and financing The research aims to test how the influence of e-commerce, accounting registration, and people's enterprise credit (KUR), on the viability of UMKM Troso fabric business in Jepara. The sample used in this study is 90 UMKM Troso fabric. The sampling technique used in this study uses random probability samplings, (simple random sampling). This research is quantitative descriptive research. The data collection technique used is the dissemination of questionnaires. The research data was analyzed using SEM-PLS analysis method with the help of the SmartPLS3.2.9 program. The results of this study found that e-commerce, accounting records, and people's enterprise credit have a positive and significant impact on business sustainability. For future researchers it is expected to be able to add other variables that can affect the sustainability of enterprises, such as knowledge of entrepreneurship, financial literacy, credit financial management and other variable.